2018
DOI: 10.1049/iet-spr.2016.0671
|View full text |Cite
|
Sign up to set email alerts
|

5G: performance and evaluation of FS‐FBMC against OFDM for high data rate applications at 60 GHz

Abstract: This study presents a frequency spreading filter bank multi-carrier (FS-FBMC) waveform as a potential candidate for the fifth generation (5G) network applications at millimetre-waves (mmWaves). The proposed model is developed based on the orthogonal frequency division multiplexing (OFDM) waveform standardised by IEEE 802.15.3c for 60 GHz high data-rate applications. The effects of non-linearities of power amplifiers (PAs) at 60 GHz for both OFDM and FS-FBMC are presented and compared using a realistic PA model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…′ is the transpose operator and the th symbol over th sub-carrier is denoted , . It is noticed that in an OQAM-FBMC system, real symbols are transmitted at interval 2 [8], where, is the time period of an OQAM-FBMC symbol. The OQAM mapping of the complex input symbol vectors…”
Section: Model Systemmentioning
confidence: 99%
“…′ is the transpose operator and the th symbol over th sub-carrier is denoted , . It is noticed that in an OQAM-FBMC system, real symbols are transmitted at interval 2 [8], where, is the time period of an OQAM-FBMC symbol. The OQAM mapping of the complex input symbol vectors…”
Section: Model Systemmentioning
confidence: 99%
“…Fig. 2 shows the 3D plots of the inverse of the cost function (8) supposed that the exact CFOs ε 1 = − π/30 and ε 2 = π/20 at SNR = 20 and 30 dB, respectively. We plotted the inverse of the cost function because the plot of the cost function is a valley-like surface which is difficult to be examined.…”
Section: Performance Of the Proposed Cfo/channel Estimatementioning
confidence: 99%
“…In addition, PHN has more prominent effect on the system performance at high data rate and/or high frequencies, e.g. 5G mmWave wireless systems [8]. To deal with these problems, a number of efficient PHN estimation techniques for compensating the channels have been proposed [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of high PAPR is even more significant in 5G systems, since 5G systems are planned to rely on utilizing mm-wave frequency ranges, to be able to satisfy the demand for large bandwidth [27]- [29]. It was shown that mm-wave power amplifiers perform poorly, and produce higher levels of distortion upon operating in the saturation region [1], [30], [31]. Therefore, PAPR minimization is highly crucial in 5G OFDM-based systems.…”
Section: Introductionmentioning
confidence: 99%